ANALISIS KEBANGKRUTAN PERUSAHAAN BERBASIS LAPORAN ARUS KAS PADA PERUSAHAAN SUB SEKTOR PERDAGANGAN BESAR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Puput Hariyo Prabowo (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2015)
The aims of this research is to examines the companies financial condition about using bankruptcy analysis based cash flow statement model with theories from Bhandary and Rajesh (2013). As for the components of the ratio-ratio model of bancrupty analysis based cash flow statement is the operating cash flow divided by current liabilities ratio, the cash flow coverage of interest ratio, the operating cash flow margin ratio, the operating cash flow return on tottal assets ratio, the earning quality ratio, quick ratio or acid test ratio, the 3 year sales growth ratio. The population in this research is the wholesale sub sector company listed on the Indonesia stock exchange. Methods of sampling used is purposive sampling. The sample in this study is 26 wholesale sub sector company listed on the Indonesia stock exchange in 2011 up to the year 2013. Methods of analysis in this study i.e. by doing the calculations using the bankruptcy analysis based cash flow statement method. The calculations show that there is no company that went bankrupt in the future, there are 14 companies that get into negative grey area, 9 companies get into positive grey area and 3 companies predicted would not be bankrupt in the future. Keywords: bankruptcy analysis, cash flow, Indonesian stock exchange and Wholesale company.